Rethinking HIV-prevention for school-going young people based on current behaviour patterns - Maretha Visser (Taylor & Francis Group, 2017)
The aim of the research was to gain increased knowledge regarding the sexual risk behaviour of school-going young people in South Africa after two decades of HIV-education in schools, to contribute to the development of improved HIV prevention strategies. In collaboration with the Department of Education, a sample of 5305 learners (between 10 and 18 years in Grades 5-12) from high-risk communities were identified. They completed a survey that assessed self-reported sexual risk behaviour and variables that potentially underlie sexual risk, such as attitudes towards preventive behaviour, perceived social norms and self-efficacy (based on the theory of planned behaviour [TPB]) and social factors like caregiver relationships and gender norms (based on the social ecological theory). Lifetime sex was reported by 49.4% of boys and 30.5% of girls in Grades 8-12, while 56% of the sexually active young people reported consistent condom use. Accurate knowledge about HIV transmission was low (37.8%). Regression analysis showed that risk behaviour was more prominent among older male youths, who perceived social norms as encouraging sexual activity, who use alcohol excessively, and who have negative attitudes towards abstinence. Perceived traditional community gender norms and negative relationships with caregivers were also associated with sexual risk behaviour. This research showed that the TPB can be used in planning HIV prevention interventions for young people. It also revealed that HIV-prevention strategies should focus beyond educating the individual, to address community factors such as improving caregiver relationships, the culture of substance abuse, peer group norms and inequality in community gender norms. These community processes influence young people's behaviour and need to be addressed to allow the youth to make healthy behavioural choices.